Pembangunan Geo-Augmented Reality untuk Pengembangan Pembelajaran Geografi Berbasis Project Based Learning - Arie Yulfa; Dian Adhetya Arif; Ernawati Ernawati; Bigharta Bhekti Susetyo; Bayu Wijayanto; Adek Andreas; Firma Maulidna; Thuba Imam Fauzi (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Learning competence as an indicator of learning process achievement must be supported by appropriate learning media. There is little innovation in the development of geography learning media, and geography teachers' use of technology is still limited and ineffective. Making Augmented Reality-based learning media is one option for achieving the desired competencies. Geo-Augmented Reality technology is developed in stages, including the study of Prototype design theory, sketching out the Prototype, and continuing with the prototyping process. The Prototype is then used in conjunction with offline learning designs to provide a detailed model of field conditions for Geo-Augmented Reality media. Implementing this media-based learning is critical in order to meet the predetermined indicators of achievement of the geography learning process.